Asialoerythropoietin Prevents Contrast-Induced Nephropathy - Yokomaku, Yukiyo (American Society of Nephrology, 2008)
Strategies to prevent contrast-induced nephropathy (CIN) are suboptimal. Erythropoietin was recently found to be cytoprotective in a variety of nonhematopoietic cells, so it was hypothesized that the nonhematopoietic erythropoietin derivative asialoerythropoietin would prevent CIN. Nephropathy was induced in rats by injection of the radiocontrast medium Ioversol in addition to inhibition of prostaglandin and nitric oxide synthesis. Administration of a single dose of asialoerythropoietin before the induction of nephropathy significantly attenuated the resulting renal dysfunction and histologic renal tubular injury. Contrast-induced apoptosis of renal tubular cells was inhibited by asialoerythropoietin both in vivo and in vitro, and this effect was blocked by a Janus kinase 2 (JAK2) inhibitor in vitro. Furthermore, phospho-JAK2/signal transducer and activator of transcription 5 (STAT5) and heat-shock protein 70 increased after injection of asialoerythropoietin, suggesting that the effects of asialoerythropoietin may be mediated by the activation of the JAK2/STAT5 pathway. Overall, these findings suggest that asialoerythropoietin may have potential as a new therapeutic approach to prevent CIN given its ability to preserve renal function and directly protect renal tissue.